Preparation, Characterization, and Activation of Co-Mo/Y Zeolite Catalyst for Coal Tar Conversion to Liquid Fuel - Didi Dwi Anggoro; Luqman Buchori; Giveni Christina Silaen; Resti Nur Utami (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
One of many efforts to convert coal tar into alternative liquid fuel is by hydrocracking. This research aims to determine the impregnation of Co-Mo/Y zeolite, its characteristics, the effect of impregnation temperature and time, and also the best Co-Mo/Y zeolite impregnation condition for the conversion of coal tar. This research was conducted in several steps, impregnating Co from Co(NO3)2.6H2O and Mo from (NH4)6Mo7O24.4H2O into Zeolite Y in liquid media, drying at 100 °C for 24 hours, and calcination at 550 °C for 3 hours. Coal tar was then reacted with hydrogen gas (as a reactant), and Co-Mo/Zeolite Y (as a catalyst) was conducted at 350 °C. Characteristic analysis showed that Co and Mo had impregnated into the Y zeolite, as well as it made no change of catalyst’s structure and increased the total acidity. The higher of impregnation temperature was increased the catalyst crystallinity, total acidity, and yield of gasoline. The longer impregnation time was reduced crystallinity value, but total acidity and yield were increased. GC analysis showed that products included into the gasoline product (C8, C9, and C10).